Performance of sugarcane bagasse activated carbon in removing oil and grease from wastewater - Rubyyatul Adhyah, Muhamad Nur (2019)
Oil and grease are one of the examples of a pollutant that can cause a severe environmental problem. The highest concentration of oil and grease inside the sewer system can cause the sewer to clog that can lead to overflow. There are various methods of oil and grease removal; one of the examples is by using adsorption method. This method commonly uses activated carbon that is one of the effective adsorbents. However, the cost for activated carbon is expensive and therefore a study was conducted by using agricultural residues as alternative adsorbents. The main objective of this study was to determine the optimum capacity of sugarcane bagasse activated carbon (SBAC) as bio-adsorbent in treating domestic wastewater. Besides, it also aims to compare the effect of size, adsorbent dosage, initial pH value of wastewater sample and contact time in the removal of oil and grease. This study also analyse the adsorption study based on dosage, pH level and contact time by using Langmuir adsorption equation. Langmuir adsorption model was used which is confirmed by a linear plot of Ce/qe against Ce. The results showed that optimum adsorption capacity for both 600μm and 1.18mm of SBAC are 3.0g with the pH level 4 for 600μm of SBAC and pH level 8 for 1.18mm of SBAC. Meanwhile, in term of contact time effect shows that both of SBAC sizes adsorbent adsorption rate increase gradually and reach optimum adsorption after 90 minutes of contact time. This study revealed that the best size of SBAC that can be used as an adsorbent of oil and grease is 600μm as it can absorb more oil and grease particles compare to 1.18mm of SBAC.